What's the mindset? An investigation of junior hockey players' attitudes toward sport psychology - Shaw, A. S. (University of Lethbridge, 2015)
In this study, 114 Canadian junior hockey players` attitudes toward sport psychology were investigated. Participants provided demographic information and completed two questionnaires. Results indicate that Canadian junior hockey players are willing to utilize sport psychology services, prefer sport psychologists as opposed to other psychological professionals, do not express stigma toward sport psychologists, and are confident in the efficacy of sport psychology; however, express an unwillingness to disclose personal information. Participants identified strongly with a growth mindset, and a positive correlational relationship was found between a growth mindset and confidence in the efficacy of sport psychology. Participants did not identify strongly with a fixed mindset; however, increased identification with a fixed mindset is associated with increased stigma, decreased personal openness, and decreased confidence in sport psychology. Ultimately, Canadian junior hockey players hold positive attitudes toward sport psychology and express interest in using sport psychology services to optimize performance and mental health.